Nah am Boden. Privater Hausbau zwischen Wohnungsnot und Landkonflikt im Samarkand der 50er- und 60er-Jahre - Petrova, Mariya (ANOR Central Asian Studies, 2021)
This study examines private homebuilding as a specific conflict-laden form of urbanization in post-Second World War Soviet Central Asia, based on the example of Samarkand. It elucidates the neglected role of private initiatives in Soviet urban planning and housing policy, which it describes as a tension-filled realm of conflicting interests, urban development tasks, and pressures.